RBTT-08. A RANDOMIZED PHASE 2 OPEN LABEL STUDY OF NIVOLUMAB PLUS STANDARD DOSE BEVACIZUMAB VERSUS NIVOLUMAB PLUS LOW DOSE BEVACIZUMAB IN RECURRENT GLIOBLASTOMA (GBM). (11th November 2019) - Ahluwalia, Manmeet; Fallah, Jaleh; Peereboom, David; Schilero, Cathy; Ali, Assad; Forst, Deborah; Wong, Eric; Wen, Patrick; Reardon, David
Abstract: INTRODUCTION: Initial trials with anti-PD1 in recurrent glioblastoma showed limited efficacy. Vascular endothelial growth factor (VEGF) is a highly upregulated proangiogenic growth factor in GBM that contributes to tumor-associated immunosuppression by inhibition of dendritic cell maturation and antigen presentation, induction of apoptosis of CD8+ T-cells and enhancing Treg activity. Hence, a combination of anti-PD1 and anti-VEGF is promising approach in recurrent GBM. METHOD: This is a 90 patient randomized, open-label, phase 2 safety study of Nivolumab and bevacizumab administered according to standard and reduced dosage schedules in patients with first recurrence of GBM. Patients will undergo 1:1 randomization to receive treatment with either Nivolumab (240 mg flat dosing IV every 2 weeks) and bevacizumab administered according to standard (10 mg/kg IV every 2 weeks; Arm A) and reduced (3 mg/kg IV every 2 weeks; Arm B) dosage schedules for recurrent glioblastoma patients. The study will allow patients that require dexamethasone up to 4 mg/day to participate in the study. All subjects will be followed for safety and tolerability, tumor progression and overall survival. Tumor progression or response endpoints will be assessed using the Radiologic Assessment in Neuro-Oncology (RANO) criteria and an exploratory endpoint will evaluate the response endpoints using the Immunotherapy RANO (iRANO). Treatment with study medication will continue until confirmed tumor progression, unacceptable toxicity or death. It is expected that enrollment and follow-up of randomized subjects (45 subjects in each arm) will take approximately 12months. The one-sample log-rank test will be applied to outcomes observed for each arm individually to test the hypothesis that OS has been improved beyond the null 12-month survival rate of 45%. With N=45 patients per arm, a one-sided test provides power=0.80 to detect survival rate of 58% at 12-months following treatment at the 0.10 significance level. The study (NCT03452579) is ongoing and enrolling patients.